Short Forms of the Centrality of Religiosity Scale: Validation and Application in the Context of Religious Individualism of Orthodox and Pentecostal Christians in Romania - Ackert, Michael (Religions, 2021)
This article presents a validation study of the short forms of the Centrality of Religiosity Scale (CRS) in Romania, followed by an examination of religious individualism among Orthodox and Pentecostal Christians. In a first step, the validity and reliability of the short forms of the CRS, namely the Abrahamitic CRS-5 and the interreligious CRSi-7, are tested in Romania. In a second step, the differences in attitudes regarding calling—a Weberian concept—are examined between Orthodox and Pentecostal Christians in Romania. For these examinations, we used data from a survey conducted in Romania in 2018 (N=547). The results show that the CRS performs well in the Orthodox (n=273) and Pentecostal subsamples (n=274). Moreover, based on the applied confirmatory factor and path analyses, on the one hand, we propose that calling attitudes stand out among Pentecostal Christians compared to Orthodox Christians. On the other hand, the Orthodox Christians make more use of religious advisers (priests), hereby expressing a different individual religious attitude of preferring to be advised rather than called. Furthermore, path analyses suggest that calling has neither a direct nor an indirect effect on religiosity among the Orthodox Christians while Pentecostal Christians’ religiosity is not directly linked to an adviser but to calling. The gender of the respondents is identified as a factor that is, directly and indirectly, related to religiosity. The results are discussed in the frame of religious individualism.